Exploring tertiary education ESL learners’ dependency on the internet, internet sources, and internet source reliability / Tg Nur Liyana Tengku Mohamed Fauzi ... [et al.] - Tengku Mohamed Fauzia, Tg Nur Liyana; Ayzan Ayub, Siti Ainul; Wan Mohamed, Wan Nazihah; Mohamad, Mimi Mazlina (Universiti Teknologi MARA, Kedah, 2024)
This study focuses on Malaysian ESL learners in a public college and aims to investigate the learners’ reliance on the Internet, the availability of Internet sources and the reliability of Internet sources. Data for the study were collected using a questionnaire that included items from two sources: a study on students' dependence on Internet sources and Online Student Engagement (OSE). A Google form was used to avoid missing values. A total of 101 responses were collected from the current semester's English writing course. The study shows that while most respondents spend an inordinate amount of time online (M=5.43; SD=1.344), they also rely on the Internet for decision making (M=5; SD=1.442). The majority tend to validate online information (M=4.66; highest M=5.69). Participants prefer authorized content (M=5.61) and reputable domains (M=5.53). Preferences and reliance on internet sources show consistent responses (SD range: 1.13-1.77), emphasizing the need to verify the accuracy of information. In conclusion, this study provides valuable insights into the Internet usage behavior of Malaysian ESL learners in a public college. The comprehensive examination of dependency, source availability and reliability underscores the multifaceted role of the Internet in their academic endeavors. The findings highlight the importance of ensuring the accuracy of information and the impact this has on improving ESL learners' learning strategies. Future research could further explore the effectiveness of interventions to minimize excessive Internet use while maximizing the positive impact on language learning outcomes.